Introduction: Special Issue ‘Complexity and Truth’ - Altmann, Philipp; Peters, Robert (Journal of Sociocybernetics, 2018)
If not even earlier, then at the latest when Oxford Dictionaries selected ‘post-truth’ as Word of the Year 2016, did the global public become aware that ‘truth’ is not an uncontested and finite concept but a social construct. Are we, then, standing on the threshold of a new ‘post-truth age’ as – for instance – The Independent has claimed? (Norman 2016) Certainly, the Word of the Year 2016 has cast a bright light onto the case that there is not ‘one truth only’ but that there are facts that can be interpreted – or rejected – in different ways. This means that truth is ‘produced’, but is it produced as scientific or religious truth or as political truth? Just think of `fake news´ and its strategic use in influencing elections, as in the case of the latest presidential elections in the US or Brazil, or the leave campaign in the case of the Brexit referendum. Thus, the production of truth is undertaken by society, at least on the level of concrete actions. This situation becomes more complicated if we consider modern complex society. The increasing globalization of economies and societies has made the world more complex than it has ever before been.